MODERNIZATION, OPTIMIZATION, BUREAUCRATIZATION... WHAT AWAITS HIGHER SCHOOL TOMORROW? - Lyudmila F. Krasinskaya (Высшее образование в России)
The article analyzes the negative trends in higher education development in the country caused by a change in the state education policy in terms of crisis, the optimization of financial costs, the intensification of the authoritarian-bureaucratic methods of educational institution management. The article adduces the results of the investigation on teachers' assessment of the modern state in higher school, the main directions of education reforms. The research touched on the issues concerning motivation and psychological climate in labor collectives in conditions of the implacable cutting down of the University network due to so called "optimization" of higher education institutions, bureaucratization of higher school activities. The author strongly argues that the continuous reforming of education system has not brought positive results, and expresses a hope in positive changes in this sphere owing to the inner capability of the pedagogical community.